Radiation-induced structural changes in chalcogenide glasses as revealed from Raman spectroscopy measurements - Kavetskyy, T.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Radiation-induced structural changes in the chalcogenide glasses of (As₂S₃)x(GeS₂)₍₁₋х₎ system with x = 0.1, 0.2, 0.4, and 0.6 corresponding to the chemical compositions Ge₂₈.₁₂₅As₆.₂₅S₆₅.₆₂₅, Ge₂₃.₅As₁₁.₈S₆₄.₇, Ge₁₅.₈As₂₁S₆₃.₂, and Ge₉.₅As₂₈.₆S₆₁.₉, respectively, were studied using the Raman spectroscopy technique in detail. The polarized (VV) and depolarized (VH) Raman spectra were recorded separately for two identical samples in the unirradiated and γ-irradiated states which allowed performing all measurements under the same experimental conditions. The Raman spectra were considered in the regions of high-frequency excitations related with the molecular peak, and low-frequency excitations related with the boson peak. The depolarization ratio spectra for the unirradiated and y-irradiated samples were examined, too. The differential Raman spectra in the high-frequency region between unirradiated and y-irradiated samples were obtained only in the VH configuration, since no spectral variations in the VV configuration were detected for all the compositions studied. Employing the differential representation (Rirrad - IRunirrad.) of the VH Raman spectra measured for the y-irradiated ( IRirrad. ) and unirradiated ( IRunirrad. ) samples, it has been found out that the radiation-induced structural changes are significant only for the glass composition with x = 0.4, while these changes are practically absent in the case of the glass compositions with x = 0.1, 0.2, and 0.6. The applied differential procedure allows also to detect the radiation-induced effects in clusters of corner-shared and edge-shared tetrahedral, which was not possible with IR Fast Fourier Transform spectroscopy due to different activity of IR and Raman bands. In addition, it was shown that the controversial companion Ac₁ mode at 370 cm⁻¹ to the main 340 cm⁻¹ A₁ symmetric mode of vibrations in cornershared tetrahedra seems to be related mainly to the vibrations of edge-shared tetrahedra. The possible nanoscale structural mechanism to account for these spectral changes has been discussed.